2015
DOI: 10.4111/kju.2015.56.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Community-based research on the benign prostatic hyperplasia prevalence rate in Korean rural area

Abstract: PurposeWe investigated the prevalence rate of benign prostatic hyperplasia (BPH) among Korean males in a rural area through a cross-sectional, community-based epidemiologic survey and analyzed the correlation with epidemiologic factors.Materials and MethodsA total of 779 males who lived in Yangpyeong County participated in a prostate examination campaign. Targeting these men, we collected the International Prostate Symptom Score (IPSS), medical history, demographic information, serum prostate-specific antigen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
0
19
1
1
Order By: Relevance
“…For example, in the study by Trueman and colleagues 25 , the presence of BPH was assessed using a self-administered questionnaire. In contrast, a study by Goh and associates 40 in Korea reported a prevalence rate of 20%. Participants were surveyed by trained investigators and prostate disease was assessed by a physical examination and measurement of prostate volume and serum prostate specific antigen.…”
Section: Discussionmentioning
confidence: 81%
“…For example, in the study by Trueman and colleagues 25 , the presence of BPH was assessed using a self-administered questionnaire. In contrast, a study by Goh and associates 40 in Korea reported a prevalence rate of 20%. Participants were surveyed by trained investigators and prostate disease was assessed by a physical examination and measurement of prostate volume and serum prostate specific antigen.…”
Section: Discussionmentioning
confidence: 81%
“…All patients had transrectal ultrasonographic evidence of BPH with prostate volume of 25 ml or above that was consistent with BOO [9]. Patients were divided into three groups according to the results of urodynamic study (UDS) just before the surgery: one comprised patients with BOO-only and others comprised patients with BOO and detrusor dysfunction.…”
Section: Methodsmentioning
confidence: 99%
“…In a Korean study, there were 2 patients (4.4%) in the 40-49 years group, 18 patients (10.9%) in 50-59 years group, 44 patients (22%) in the age group of 60-69 years group and 56 patients (26.6%) above the age of 70 years. 4 The prevalence of BPH was 21.0% overall: 11.6% among subjects aged 50 to 59 years, 18.1% for those aged 60 to 69, 30.8% for those aged 70 to 79 and 50.8% among those aged 80 years or more. Compared with previous studies in urban or rural areas, the prevalence was slightly lower.…”
Section: Resultsmentioning
confidence: 99%